2021
DOI: 10.3390/en14092426
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of System-Level Energy Harvesting Characteristics of a Thermoelectric Generator Operating in a Diesel Engine Using Artificial Neural Networks

Abstract: This study evaluated the potential of artificial neural networks (ANNs) to predict the system-level performance of a thermoelectric generator (TEG), whose performance depends on various variables including engine load, engine rotation speed, and external load resistance. Therefore, a Python code was developed to determine an optimal ANN structure by tracking the training/prediction errors of the ANN as a function of the number of hidden layers and nodes of hidden layers. The optimal ANN was trained using 484 o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 18 publications
1
5
0
Order By: Relevance
“…Last but not least, the use of the best-segmented ratio design in a thermoelectric generator system showed improved performance and boosted output power by 6.8%. Kim et al estimated the performance of a TEG running on a diesel engine using ANNs implemented using Python code [100]. Validation studies found a 3.49% difference between the output power of the experimental and predicted TEG.…”
Section: Machine Learning Studies Focus On Electrical Transport Prope...mentioning
confidence: 99%
“…Last but not least, the use of the best-segmented ratio design in a thermoelectric generator system showed improved performance and boosted output power by 6.8%. Kim et al estimated the performance of a TEG running on a diesel engine using ANNs implemented using Python code [100]. Validation studies found a 3.49% difference between the output power of the experimental and predicted TEG.…”
Section: Machine Learning Studies Focus On Electrical Transport Prope...mentioning
confidence: 99%
“…where 𝜌 𝐽 ⃗ is the Joule heating, 𝛼𝐽 ⃗ ∇𝑇 is the work done against the Seebeck field, and 𝑞 = [ℎ𝑃(𝑇 − 𝑇 )]/𝐴 is the heat loss on the side of the TEG's legs due to convection, where the term ℎ [W/m K] is the heat transfer coefficient, 𝑇 the ambient temperature, 𝑃 and 𝐴 are the perimeter and area of the TEG's leg cross-section, respectively [28]. The divergence of Equation (3) using the product rule yields (7).…”
Section: Governing Equationsmentioning
confidence: 99%
“…A single thermoelectric generator (TEG) is a device composed of semiconductor materials (N and P-type) connected electrically in series and thermally in parallel (More than two modules can be electrically connected either in series or parallel) that produces electric power from a temperature difference (Seebeck effect), or cooling from an electric potential source (Peltier effect) [1]. These devices are used in a wide range of applications i.e., bio-integrated wearable devices [2], pipe heat energy waste [3], automobile exhaust heat [4,5], heat exchangers [6], combustion engines [7,8], photovoltaic systems [9][10][11], and space exploration [12][13][14].…”
Section: Introductionmentioning
confidence: 99%
“…The field of ML has gained increased interest in recent years, especially with the advent of neural networks that seek to transition the world from artificial narrow intelligence to artificial general intelligence [40]. The merits of ML over the conventional modelling tools used to analyze the performance of energy conversion devices like standalone PVs [41][42][43] and TEMs [44][45][46] have been comprehensively discussed in literature. Issues like modelling complexity, computational time consumption, massive energy requirements, and even deployment ease have been reportedly solved using ML [47][48][49].…”
Section: Introductionmentioning
confidence: 99%